A practical guide to estate planning and administration - Michael J. Gau (Thomson/Delmar Learning, 2005)
This text was written by an attorney and experienced paralegal instructor who applied his first-hand knowledge of estate planning in developing this engaging look at the subject. He designed this practical, step-by-step guide by discussing and defining concepts and issues in the context of three fictional families. Enabling students to relate theoretical concepts to "real-life" scenarios in this way is a proven manner of enhancing learning, retention and application of the material. Through this method, students will learn about traditional estate planning documents such as wills, trusts, and powers of attorney. And, they will consider alternatives to formal estate planning documents including gifts, contracts, and beneficiary designations. This guide emphasizes practical concerns of drafting estate planning documents, and provides numerous examples of such documents for students to examine and apply to the estate planning efforts for the text's three fictional families